2022
DOI: 10.1038/s41598-022-16497-5
|View full text |Cite
|
Sign up to set email alerts
|

Organic and in-organic fertilizers effects on the performance of tomato (Solanum lycopersicum) and cucumber (Cucumis sativus) grown on soilless medium

Abstract: The effects of organic fertilizers, based on Tithonia diversifolia, and in-organic fertilizers, based on hydroponics fertilizer, were evaluated on the performance, leaves, and fruit mineral concentrations of tomato (Solanum lycopersicum) and cucumber (Cucumis sativus) plants grown under soilless medium in a screen house. The treatments comprised six levels of liquid organic fertilizer (5, 15, 25, 35, 45, 55 mL), in-organic fertilizer, and a control. Both organic and in-organic fertilizers increased the growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Pakpahan, HB, and Mahmudah [44] argue that the recommended concentration of nutrients for good growth of Pagoda mustard is 1400 ppm. Recently, several researchers have directed their studies in an environmentally friendly direction by using liquid organic fertilizers as alternative nutrients for hydroponics [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Pakpahan, HB, and Mahmudah [44] argue that the recommended concentration of nutrients for good growth of Pagoda mustard is 1400 ppm. Recently, several researchers have directed their studies in an environmentally friendly direction by using liquid organic fertilizers as alternative nutrients for hydroponics [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Stem diameter from the beginning of observation (14 DAP) to the end of observation (49 DAP) with mean value 5.30 mm to 12.10 mm. The previous study from Adekiya et al (2022) reported that inorganic fertilizer was better than organic and that stem diameter had a higher value. The availability of several elements caused N, P, K, Ca, Mg, and Fe more in inorganic fertilizer.…”
Section: Articlementioning
confidence: 91%
“…Sin embargo, es importante tener en cuenta que cada región puede requerir prácticas de cultivo y manejo específicas para maximizar su rendimiento. Según la FAO el 46,21% y 46,27% de los participantes de un estudio indicaron que la fertilización adecuada y periódica en pepino, en tiempos oportunos, solamente es necesario, siempre y cuando se cuente con una asesoría profesional para determinar la composición adecuada del fertilizante 12 .…”
Section: Introductionunclassified